The Role of The Madrasah Diniyah Teacher on Implementing The Values of Religious Moderation - Wonadi Idris (Ambarsa : Jurnal Pendidikan Islam, 2022)
One of the objectives of holding Madrasah Diniyah (Madin) is to prepare students to be able to master Islamic religious knowledge. Islam with good and correct understanding and practice. Islam invites its people or followers to behave tawasuth, which means in the middle or balanced, not extreme and not inclusive. This attitude of tawasuth is part of religious moderation that must be instilled in students so that they have a moderate attitude in the life of the nation and state. For the Indonesian people, this basic attitude is very much needed as an investment for students to behave and act straight and always constructive and avoid all forms of tatharruf (extreme) approaches. The involvement of madrasah diniyah teachers in providing an understanding of the attitude of tawasuth for students needs to be cultivated and echoed. Islamic religious education material is emphasized on an understanding of compassion, mutual love, mutual respect, and mutual help in goodness. Because with this understanding, students can implement it in everyday life. This paper discusses the role of madrasah diniyah teachers in instilling religious moderation. This paper uses a library research method with a descriptive approach.